Strategi Komunikasi Pembangunan dalam Adopsi Inovasi Teknologi Pertanian Modern untuk Swasembada Pangan di Kabupaten Sukoharjo - Estu Widiyowati; Meta Dewi Adhiva; Sihabuddin (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2026)
Food self-sufficiency remains a strategic issue in Indonesia amidst population growth, climate change, and the increasing demand for agricultural productivity. Although the government has promoted agricultural modernization through the adoption of modern agricultural technologies, the level of technology adoption among farmers remains uneven. Previous studies have primarily focused on technical, economic, and institutional factors, while the role of development communication in facilitating technology adoption has received limited attention. This study aims to analyze the development communication strategy implemented by the Department of Agriculture and Fisheries of Sukoharjo Regency in encouraging the adoption of modern agricultural technology to support food self-sufficiency. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving agricultural extension officers, government officials, and farmer groups. Data were analyzed using the interactive model of Miles and Huberman. The findings reveal that the diffusion of innovation is influenced by four key elements: innovation, communication channels, time, and social systems. Interpersonal communication through agricultural extension workers serves as the most effective channel in building farmers’ knowledge, trust, and willingness to adopt technology. The adoption process occurs gradually through the stages of knowledge, persuasion, decision, implementation, and confirmation, while farmer groups and local opinion leaders play significant roles in accelerating innovation diffusion. The study concludes that development communication functions not only as an information dissemination mechanism but also as a participatory instrument that bridges government policies and farmers’ socio-cultural realities, thereby supporting the successful adoption of modern agricultural technology and strengthening food self-sufficiency programs.